A Need for affordable housing in Banda Aceh, Indonesia - Nova Iriansyah (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
Banda Aceh recently received Adiupaya Puritama award, an award given by the Housing Ministry for cities that have successfully manage its housing and settlement. While there is no doubt that Banda Aceh has made a good achievement in terms of providing housing for its residents, there is always a room for an evaluation of the previous and upcoming policy to improve and to develop a more effective housing policy. Similar to many cities in Indonesia, Banda Aceh experience massive urbanization although in a much smaller scale compare to Jakarta or Surabaya. This has been affected housing stocks in Banda Aceh, in particular the need for more affordable housing for low income residents, which were mostly provided during the tsunami reconstruction program. On the other hand, there is an intense plan to develop a vertical housing (Rusun) to fulfil the need for affordable housing for the public as the land price is increasing. This paper attempts to look at both available affordable housing stocks and upcoming plan of affordable housing for low income residents to support local authorities and other key players in delivering higher quality of affordable housing in Banda Aceh